lim(x->∞) (2x² - 5x + 4)/(20x - 5) = { : x } = lim(x->∞) (2x - 5 + 4/x)/(20 - 5/x) = (∞ - 5 + 0)/(20 - 0) = ∞
lim(x->1) (x + 2)/(x² + 3x + 1) = (1 + 2)/(1 + 3 + 1) = 3/5
lim(x->2) (4x² - 7x - 2) / (5x² - 9x - 2) = lim(x->2) (4x + 1)(x - 2)/ (5x + 1)(x - 2) = lim(x->2) (4x + 1)/ (5x + 1) = (4*2 + 1)/(5*2 + 1) = 9/11
разложим 4x² - 7x - 2 = (4x + 1)(x - 2)
D = 49 + 4*4*2 = 81
x12 = (7 +- 9)/8 = 2 -1/4
5x² - 9x - 2 = (5x + 1)(x - 2)
D = 81 + 4*2*5 = 121
x12 = (9 +- 11)/10 = 2 -1/5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
lim(x->∞) (2x² - 5x + 4)/(20x - 5) = { : x } = lim(x->∞) (2x - 5 + 4/x)/(20 - 5/x) = (∞ - 5 + 0)/(20 - 0) = ∞
lim(x->1) (x + 2)/(x² + 3x + 1) = (1 + 2)/(1 + 3 + 1) = 3/5
lim(x->2) (4x² - 7x - 2) / (5x² - 9x - 2) = lim(x->2) (4x + 1)(x - 2)/ (5x + 1)(x - 2) = lim(x->2) (4x + 1)/ (5x + 1) = (4*2 + 1)/(5*2 + 1) = 9/11
разложим 4x² - 7x - 2 = (4x + 1)(x - 2)
D = 49 + 4*4*2 = 81
x12 = (7 +- 9)/8 = 2 -1/4
5x² - 9x - 2 = (5x + 1)(x - 2)
D = 81 + 4*2*5 = 121
x12 = (9 +- 11)/10 = 2 -1/5